Inovasi Sistem Keamanan dan Kendali Penerangan Rumah Berbasis BLE & Telegram: Integrasi Cerdas dengan Metode RSSI Measurement - Suryowinoto, Andy; Hasyim, Muhammad; Muharom, Syahri; Candrarani, Diva (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2025)
The increasing security concerns and urban lifestyle distractions have led to negligence in home security. Consequently, innovative security systems are necessary to automatically assist homeowners in securing their homes. This research addresses this issue by proposing the implementation of an automatic door lock security system through the Bluetooth Low Energy (BLE) protocol on the NodeMCU ESP32. It aims to integrate existing home security systems with the Internet of Things platform using the Telegram Bot API, focusing particularly on access control for entering and exiting the house. By employing the Received Signal Strength Indicator (RSSI) measurement method, this research determined the ideal distance for automatic door locking by the security system. After collecting the data using one device, the researcher tested them nine times at distances ranging from 0 to 2 meters. The results indicated that the system had a detection limit at a distance of 1 meter with a signal strength value of -85 dBm. Additionally, the power consumption of the security device was measured at 1.645 mA, and the average delay time for data transmission from transmitter to receiver reached approximately 2.22 ms. In conclusion, the prototype security system in this research was successfully designed and operated according to its objectives